Expressionism / abstraction [videorecording]. (The Metropolitan Museum seminars in art, 1986)
Describes expressionism as the alteration by an artist of the appearances of his subject such that the objects are painted in obviously abnormal forms. Describes abstraction as the complete disregard of natural appearances.